Marine debris in Trindade Island, a remote island of the South Atlantic. (December 2018) - Andrades, Ryan; Santos, Robson G.; Joyeux, Jean-Christophe; Chelazzi, David; Cincinelli, Alessandra; Giarrizzo, Tommaso
Abstract: Marine debris is widespread in oceans worldwide, including the most remote locations. Here, for the first time, we report macro-debris accumulation on beaches of Trindade Island, a remote island 1160 km from mainland Brazil. High debris density was recorded on windward, east-coast beaches, which are exposed to wind-driven currents. Small-sized plastic fragments were the most abundant debris. Polyethylene (67%), polypropylene (30%) and polyamide (3%) were the most prevalent polymeric materials identified by ATR-FTIR. Identified debris show that interaction with Trindade fauna, mainly with seabirds and endangered terrestrial crabs, exists and already has some impact. This study provides baseline information on Trindade macro-debris demonstrating that the island, located on the edge of the South Atlantic Gyre, acts as a sink for gyre debris, exposing the island fauna to the threats related to plastic contamination. Graphical abstract: Highlights: Island windward beaches recorded high debris densities over 2 items.m −2 . Polyethylene and polypropylene were the main polymers identified by ATR-FTIR. Plastic colors suggested a direct harmful link between fauna and beach debris.